A contribuição do programa nacional de melhoria do acesso e da qualidade da atenção básica (PMAQ-AB), no processo de trabalho das equipes de saúde da família - Bertusso, Francielle Regina (2017)
Basic care (AB) is the main entrance for Sistema Único de Saúde (Brazil’s public health system) and must guide care on other levels of the system. In 2011, Brazilian Ministry of Health launched PMAQ-AB- Programa Nacional de Melhoria do Acesso e da Qualidade da Atenção Básica (National program for improvement of access and quality to basic care) with the intention of promoting changes in the working process of basic care staff to make it more efficient and accurate. PMAQ-AB has three stages: admission and contracting; external assessment and qualification; and re-contracting, as well as a transverse development axis which contains: self-assessment, monitoring of indicators, ongoing training, institutional support and horizontal cooperation. A complete cycle average duration is two years and, since its creation, there were two complete cycles – 2012/2013 and 2014/2015 – while the third, ongoing, started in 2016. At Parana state’s tenth regional section of public health, 27 staffs of ESF - Estratégia de Saúde da Familia (Family health strategy program), participated in the two first cycles. Present field and document research, aims at analyzing possible changes occurred in the working process of ESF staffs who took part in the first and second cycles PMAQ-AB, in cities covered by the same Regional section of public health. To all universities that participated in the gathering of data at this stage of the program, it was possible to use the data bank of external assessments, on which the documental part of this research based itself. Field research consisted of a semi-structured interview with 21 ESF professionals who participated in the two first cycles of the programs. Quantitative data were analyzed according to simple descriptive statistics while the analysis of qualitative ones considered their content. Results showed both positive and negative effects of the program. As positive changes, it is possible to mention a better comprehension on PMAQ by basic care staffs, which reduced distress after external assessment process; organizing and registration of information generated by the staff; territorializing area of influence; scheduled client service and reception. However, when it comes to protocol use; staff meetings and local planning, very few changed. The adoption of PMAQ-AB, mostly results from the fact that it is linked to transfers of Federal funds to the cities, which represents an important input of funds to basic care, then it must be kept as well as expanded. The suggestion, therefore, is that there is bigger involvement of the staffs on the process of contracting of indicators alongside with new empirical studies. These should collate secondary data with field research data, to identify both convergent and different points and to reassess aspects of the program itself.